The Time Course of Markers of Neutrophil Extracellular Traps in Patients Undergoing Revascularisation for Acute Myocardial Infarction or Stable Angina Pectoris - Ragnhild Helseth; Svein Solheim; Harald Arnesen; Ingebjørg Seljeflot; Trine Baur Opstad (Mediators of Inflammation)
Background and Aims. Neutrophil extracellular traps (NETs) have been identified in acute myocardial infarction. We assessed the time profile and association with infarct size for NETs markers in ST-elevation myocardial infarction (STEMI) and stable angina pectoris (AP). Methods. In 20 patients with STEMI and 10 with AP undergoing percutaneous coronary intervention (PCI), blood samples were collected before PCI (only AP group) and after 3 and 12 hours, days 1, 3, 5, 7, and 14 for measurement of NETs markers. Results. Double-stranded deoxyribonucleic acid (dsDNA) and nucleosome levels were higher in STEMI than AP until day 3 and 12 hours (p<0.03, all). DsDNA declined after day 5 in both groups (p<0.04, all), while nucleosomes declined until day 3 only in the AP group (p<0.05, all). DsDNA correlated with peak troponin T and creatine kinase MB (CKMB) at day 5 (r=0.48, p=0.03, both) and with MRI-measured infarct size at days 5 and 7 (r=0.61, p=0.01 and r=0.52, p=0.04, resp.), while nucleosomes correlated with infarct size at day 5 (r=0.58, p=0.02). Conclusions. High levels of NETs markers were observed in STEMI shortly after revascularisation and were partly associated with infarct size. The decline thereafter in both groups indicates a role for NETs in both acute and chronic atherothrombosis.